The symbiosis between information system project complexity and information system project success - Marnewick, Carl (AOSIS, 2017)
Project success is widely covered, and the discourse on project complexity is proliferating. The purpose of this book is to merge and investigate the two concepts within the context of information system (IS) projects and understand the symbiosis between success and complexity in these projects. In this original and innovative research, exploratory modelling is employed to identify the aspects that constitute the success and complexity of projects based on the perceptions of IS project participants. This scholarly book aims at deepening the academic discourse on the relationship between the success and complexity of projects and to guide IS project managers towards improved project performance through the complexity lens. The research methodology stems from the realisation that the complexity of IS projects and its relationship to project success are under-documented. A post positivistic approach is applied in order to accommodate the subjective interpretation of IS-project participants through a quantitative design. The researchers developed an online survey strategy regarding literature concerning the success and complexity of projects. The views of 617 participants are documented. In the book, descriptive statistics and exploratory factor analysis pave the way for identifying the key success and complexity constructs of IS projects. These constructs are used in structural-equation modelling to build various validated and predictive models. Knowledge concerning the success and complexity of projects is mostly generic with little exposure to the field of IS project management. The contribution to current knowledge includes how the success of IS projects should be considered as well as what the complexity constructs of IS projects are. The success of IS projects encompasses strategic success, deliverable success, process success and the 'unknowns' of project success. The complexity of IS projects embodies organisational complexity, environmental complexity, technical complexity, dynamics and uncertainty. These constructs of success and complexity are mapped according to their underlying latent relationships to each other. The intended audience of this book is fellow researchers and project and IS specialists, including information technology managers, executives, project managers, project team members, the project management office (PMO), general managers and executives that initiate and conduct project-related work. The work presented in this first edition of the book is original and has not been plagiarised or presented before. It is not a revised version of a thesis or research previously published. Comments resulted from the blind peer review process were carefully considered and incorporated accordingly.